GOLD-grade specific disease vharacterization and phenotyping of COPD using quantitative computed tomography in the nationwide COSYCONET multicenter trial in Germany - Konietzke, Philip; Weinheimer, Oliver; Triphan, Simon M. F.; Nauck, Sebastian; Wünnemann, Felix; Konietzke, Marilisa; Jobst, Bertram; Jörres, Rudolf A.; Vogelmeier, Claus F.; Heußel, Claus Peter; Kauczor, Hans-Ulrich; Biederer, Jürgen; et al. (Respiration, 2024)
Introduction: The aim of this study was to apply quantitative computed tomography (QCT) for GOLD-grade specific disease characterization and phenotyping of air-trapping, emphysema, and airway abnormalities in patients with chronic obstructive pulmonary disease (COPD) from a nationwide cohort study. Methods: As part of the COSYCONET multicenter study, standardized CT in ex- and inspiration, lung function assessment (FEV1/FVC), and clinical scores (BODE index) were prospectively acquired in 525 patients (192 women, 327 men, aged 65.7 ± 8.5 years) at risk for COPD and at GOLD1-4. QCT parameters such as total lung volume (TLV), emphysema index (EI), parametric response mapping (PRM) for emphysema (PRMEmph) and functional small airway disease (PRMfSAD), total airway volume (TAV), wall percentage (WP), and total diameter (TD) were computed using automated software. Results: TLV, EI, PRMfSAD, and PRMEmph increased incrementally with each GOLD grade (p < 0.001). Aggregated WP5-10 of subsegmental airways was higher from GOLD1 to GOLD3 and lower again at GOLD4 (p < 0.001), whereas TD5-10 was significantly dilated only in GOLD4 (p < 0.001). Fifty-eight patients were phenotyped as “non-airway non-emphysema type,” 202 as “airway type,” 96 as “emphysema type,” and 169 as “mixed type.” FEV1/FVC was best in “non-airway non-emphysema type” compared to other phenotypes, while “mixed type” had worst FEV1/FVC (p < 0.001). BODE index was 0.56 ± 0.72 in the “non-airway non-emphysema type” and highest with 2.55 ± 1.77 in “mixed type” (p < 0.001). Conclusion: QCT demonstrates increasing hyperinflation and emphysema depending on the GOLD grade, while airway wall thickening increases until GOLD3 and airway dilatation occur in GOLD4. QCT identifies four disease phenotypes with implications for lung function and prognosis.
Gesehen am 08.05.2025